Anti-Rationalism and Moral Revolution. Ethical Socialism of Sorel and Abramowski - Gniadek, Michał (Hybris, 2022)
The purpose of this article is to discuss and compare the social philosophy of Georges Sorel and Edward Abramowski. The analysis here concerns two major issues. The first part of the text presents the approach of these authors toward rationalism, understood as an intellectual position, whose ontological and epistemological premises affect the way we think about social, moral, and political issues. The conclusions from this analysis are used in the second and third parts of the text, devoted respectively to the notions of revolution and retrospective utopia, which both for Sorel and Abramowski have primarily ethical value. However, while Sorel subordinates the future revolution to the spontaneous, irrational action of the proletariat, which is guided by the myth of a general strike, in Abramowski’s view, this spontaneity of action is to be realized in cooperatives, syndicates, and ethical movements, which gradually educate the man of the future. What they have in common, though, is a tendency to idealize the communities that existed in the past, which for them serve as a source of moral ideals. Ultimately, it turns out that reason, being the foundation of modern society and the symbol of an attitude inclined towards simplification and abstraction, not only must be abolished, but also replaced by human freedom and creativity.